PENDIDIKAN KARAKTER DALAM METODE AKTIF, INOVATIF, & KREATIF - Ulfa Yanti Zahara; Silvya Wirnanda Rambe; Muhammad Wahyudi (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2021)
Education is a process to change the identity of a learner to be more advanced, or one of the renewal processed that has a meaningfull experience. Moral education in everyday life is often used to explain aspects related to ethics. A person’s character can be observed from 3 aspect, namely knowing goodness, loving kindness, and doing kindness. The steps for implementing character education to become a school culture, namely an agreement on the character to be achieved and targeted by the school, Build an understanding that the school wants to cultivate positive character for all school members, develop an overall plan to intensify the development and learning of the character to be achieved, and integrate selected characters into learning throughout the curriculum continuously. Value that must exist in character education such us, religious, tolerance, love peace, care for the environment, honest and anti-negotitation and violence.